Assessment of radical scavenging capacity of antioxidants contained in foods and beverages in plasma solution - Morita, Mayuko; Naito, Yuji; Yoshikawa, Toshikazu; Niki, Etsuo (Food & function, 2015)
The assessment of the radical scavenging capacity of antioxidants has been the subject of extensive studies and controversy. The aim of this study is to develop a simple and inexpensive method for the assessment of the radical scavenging capacity of antioxidants contained in foods and beverages in plasma solution, a biologically relevant heterogeneous medium. Three types of probes, hydrophilic pyranine, with low reactivity, hydrophilic pyrogallol red (PGR), with high reactivity, and lipophilic BODIPY, with moderate reactivity, were separately used to measure the amount and rate of peroxyl radical scavenging. The amount of radicals scavenged by antioxidants was assessed from the lag phase produced by antioxidants in the decay of pyranine and BODIPY, while the reactivity of the antioxidants was assessed from their effect on the decay rate of PGR. Two liquid and two solid samples were tested. Commercial bottled green tea and vegetable juice were found to scavenge 15.6 and 3.45 mmol radicals L −1 and the former scavenged peroxyl radicals 81 times faster than the latter. As for the solid samples, instant coffee powder was found to scavenge several times more radicals and more rapidly than green tea powder. This method may be applied to the assessment of the radical scavenging capacity of antioxidants contained in foods, beverages, and supplements in biologically relevant heterogeneous media. Amount and rate of scavenging radical by antioxidants contained in foods and beverages are assessed in plasma solution.